A Systematic Review of the Incidence and Outcomes of In-Hospital Cardiac Arrests in Patients With Coronavirus Disease 2019*. Issue 6 (12th March 2021) - Lim, Zheng Jie; Ponnapa Reddy, Mallikarjuna; Curtis, J. Randall; Afroz, Afsana; Billah, Baki; Sheth, Vishad; Hayek, Salim S.; Leaf, David E.; Miles, Jeremy A.; Shah, Priyank; Yuriditsky, Eugene; Jones, Daryl; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To investigate the incidence, characteristics, and outcomes of in-hospital cardiac arrest in patients with coronavirus disease 2019 and to describe the characteristics and outcomes for patients with in-hospital cardiac arrest within the ICU, compared with non-ICU patients with in-hospital cardiac arrest. Finally, we evaluated outcomes stratified by age. DATA SOURCES: A systematic review of PubMed, EMBASE, and preprint websites was conducted between January 1, 2020, and December 10, 2020. Prospective Register of Systematic Reviews identification: CRD42020203369. STUDY SELECTION: Studies reporting on consecutive in-hospital cardiac arrest with a resuscitation attempt among patients with coronavirus disease 2019. DATA EXTRACTION: Two authors independently performed study selection and data extraction. Study quality was assessed with the Newcastle-Ottawa Scale. Data were synthesized according to the Preferred Reporting Items for Systematic Reviews guidelines. Discrepancies were resolved by consensus or through an independent third reviewer. DATA SYNTHESIS: Eight studies reporting on 847 in-hospital cardiac arrest were included. In-hospital cardiac arrest incidence varied between 1.5% and 5.8% among hospitalized patients and 8.0–11.4% among patients in ICU. In-hospital cardiac arrest occurred more commonly in older male patients. Most initial rhythms were nonshockable (83.9%, [asystole = 36.4% and pulseless electrical activity = 47.6%]). Return of spontaneous circulation occurred in 33.3%, with a 91.7% in-hospital mortality. In-hospital cardiac arrest events in ICU had higher incidence of return of spontaneous circulation (36.6% vs 18.7%; p < 0.001) and relatively lower mortality (88.7% vs 98.1%; p < 0.001) compared with in-hospital cardiac arrest in non-ICU locations. Patients greater than or equal to 60 years old had significantly higher in-hospital mortality than those less than 60 years (93.1% vs 87.9%; p = 0.019). CONCLUSIONS: Approximately, one in 20 patients hospitalized with coronavirus disease 2019 received resuscitation for an in-hospital cardiac arrest. Hospital survival after in-hospital cardiac arrest within the ICU was higher than non-ICU locations and seems comparable with prepandemic survival for nonshockable rhythms. Although the data provide guidance surrounding prognosis after in-hospital cardiac arrest, it should be interpreted cautiously given the paucity of information surrounding treatment limitations and resource constraints during the pandemic. Further research is into actual causative mechanisms is needed.